Efek Moderasi Religiusitas pada Pengaruh Love of Money, Money Ethics, dan Ketidakpercayaan Kepada Fiskus Terhadap Tax Evasion - Salma Indah Safitri; Juli Ratnawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Tax evasion is one of the factors causing suboptimal tax revenue in Indonesia. This phenomenon is caused by psychological and ethical factors such as love of money, money ethics, and distrust of the tax authorities that encourage taxpayers to resist tax. This study aims to determine the moderating effect of religiosity on the influence of the love of money, money ethics, and distrust of the tax authorities on tax evasion. The study used a quantitative approach with a population of students from the Faculty of Economics and Business, Accounting Study Program, Dian Nuswantoro University, Semarang. The sampling technique used purposive sampling with data analysis through descriptive tests, data instrument tests, and moderate regression analysis (MRA). The study results showed that love of money, money ethics, and distrust of the tax authorities significantly affected tax evasion. Religiosity was shown to moderate the three relationships, where a high level of religiosity can reduce the tendency of tax evasion and increase ethics regarding money. This study contributes to understanding the factors that influence tax evasion behavior and emphasizes the role of spiritual values ​​in tax compliance.